Tales From Three 18th Century Eruptions to Understand Past and Present Behaviour of Etna - Corsaro, Rosa Anna; Branca, Stefano; De Beni, Emanuela; Tanguy, Jean-Claude (Frontiers in Earth Science, 2021)
The structure of an active volcano is highly dependent on the interplay among the geodynamic context, the tectonic assessment as well as the magmatic processes in the plumbing system. This complex scenario, widely explored at Etna during the last 40 years, is on the contrary incomplete for the recent historical activity. We focused on the activity that occurred in 1763 along the west flank of the volcano. Here, an eruption started on 6th February and formed the scoria cone of Mt. Nuovo and a roughly 4-km-long lava flow field. Another small scoria cone, known as Mt. Mezza Luna, is not dated in historical sources. It is located just 1 km eastward of Mt. Nuovo and produced a 700 m long flow field. The activity of Mts. Nuovo and Mezza Luna are intriguing to investigate for several reasons. First, the old geological maps and volcanological catalogues attribute Mt. Mezza Luna to the Mt. Nuovo eruption, while historical sources described Mt. Nuovo’s activity as producing a single scoria cone and do not give information about the formation of Mt. Mezza Luna. Second, petrologic studies highlight that the products of Mt. Mezza Luna are similar to the sub-aphyric Etna basalts, which preserve a composition relatively close to Etna primitive magma and enable insights into the deep portion of the volcano’s plumbing system. Third, the two scoria cones built up along the so-called West rift of Etna, which represents one of the main magma-intrusion zones of the volcano. Finally, La Montagnola eruption, which also occurred in 1763, along the South rift of the volcano, has been well-studied and provides useful information to be integrated with our data. We carried out a multidisciplinary study comprising a critical review of historical records, new field surveys, petrochemical analyses and petrologic modelling of the Mts. Nuovo and Mezzaluna eruptions and integrated our results with literature data. This multidisciplinary approach allowed improving the stratigraphic record of historical eruptions reported in the Mount Etna Geological map, modelling the sub-volcanic magmatic processes responsible for magma differentiation and speculating on possible inferences with the volcano tectonics of the area.